Legal challenges of Afghanistan's membership as a least developed country to WTO and the way forward - Zada, Sebghatullah Qazi
Despite the inclusion of special treatment and exception provisions in the Doha Round and the WTO agreements, the ambiguity of the implementation of these principles are rendered ineffective at some instances. There is a durable practice of decision making so-called “by consensus” by WTO, but in reality rich countries exercise immoderate influence within the body. Afghanistan as an LDC country became the 164th country to be part of WTO. However, it is uncertain how much the country could reap benefit from this membership. Thus, the objective of this research is to evaluate the efficiency of WTO's present set up and its SDT provisions towards LDCs, mainly Afghanistan. Likewise, this research aims to examine Afghanistan's legal and institutional challenges that serve as a barrier to trade and the needed reforms. This research is founded on doctrinal and non-doctrinal (empirical) research methodologies. The former is largely dependent on primary and secondary sources of WTO, textbook analysis, content analysis and reports of International Organisations while the latter is based on in-depth and semi-structured interviews. Currently, Afghanistan's legal and regulatory frameworks and enforcement mechanisms is at a terrible shape. Much of the frameworks needed for the encouragement and protection of private investment is still not in place. Its three overlapping systems Sharia (Islamic Law), Shura (traditional law and practice), and the formal legal system instituted under the 2004 Constitution can be confusing, to both investors and legal professionals, thus driving away the investors from Afghanistan. As the membership of WTO is expected to generally have a positive impact on Afghanistan, this prospect can also be hindered by severe institutional and legal weaknesses caused by Constitutional frameworks in forming executive, judiciary and legislature as well as weak institutional frameworks for the organs in charge of trade. Hence, there is a need for extensive reforms in institutional and legal frameworks of Afghanistan.